Back Cover: Structure, Function, and Inhibition of Staphylococcus aureus Heptaprenyl Diphosphate Synthase (ChemMedChem 17/2016). (6th September 2016) - Desai, Janish; Liu, Yi‐Liang; Wei, Hongli; Liu, Weidong; Ko, Tzu‐Ping; Guo, Rey‐Ting; Oldfield, Eric
Abstract : The back cover picture shows the structure of a new drug target, heptaprenyl diphosphate synthase from Staphylococcus aureus, essential for menaquinone biosynthesis. The protein contains a catalytic subunit and a small regulatory subunit and only functions as the heterodimer; it is inhibited by one of its substrates, farnesyl diphosphate, at high concentrations, as well as by lipophilic bisphosphonates; S. aureus cell growth is inhibited by the latter compounds, and is rescued by menaquinone. There are no synergistic effects with cell wall biosynthesis inhibitors, but there is synergy with fosmidomycin, in Bacillus subtilis, due to upstream targeting of isoprenoid biosynthesis in the non‐mevalonate pathway. More information can be found in the Full Paper by Eric Oldfield et al. onpage 1915 in Issue 17, 2016 (DOI:10.1002/cmdc.201600311 ).